Efficient recovery of valuable metals from lead-zinc smelting by-products by ultrasonic strengthening. (December 2022) - Xu, Yingjie; Xia, Hongying; Zhang, Qi; Cai, Wuchen; Jiang, Guiyu; Zhang, Libo
Graphical abstract: Highlight: A new leaching method of zinc and germanium was designed. The occurrence state of Ge, Fe, Si and Zn before and after leaching was shown. The leaching rate was increased by 10% and the reaction time was shortened by 50%. Lead is highly enriched and recovered. Abstract: As a byproduct of lead and zinc smelting, zinc oxide dust often contains abundant valuable metals such as zinc and germanium. To improve the leaching of zinc and germanium in sulfuric acid, the correlation between germanium and other elements in zinc oxide dust, the phase composition of the main elements, and Eh-pH dominant area of germanium were analyzed. Finally, ultrasonic waves and potassium dichromate were added to enhance the leaching of zinc and germanium in the leaching process. The results show that the best recoveries of zinc and germanium are 99.25 % and 90.44 %, respectively, under the optimum conditions. Compared with the existing process, the leaching rate is increased by 8 ∼ 10 % and the leaching time is reduced by more than 50 %. There are fewer impurities in the leaching residue after leaching, and the lead content is about 50 % and can be directly recycled back into the lead smelting process for recycling. In conclusion, the oxidation leaching of zinc and germanium from zinc oxide dust with potassium dichromate under ultrasound proves to be efficient, economical and practical.